Special Emphasis of Chinese Politics behind COVID-19 and its Impact on India-China Relations - Chongmaiha Reang; Puguh Toko Arisanto (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
The COVID-19 pandemic emerged as a global health crisis that revealed China's political strategies in intricate ways. This study examines the political aspects of China's response to the outbreak, focusing on its information management, domestic policies, and international diplomacy. By analyzing narratives surrounding the virus's origins and its global spread, the research also assessed the pandemic's impact on Indo-China relations[1] across diplomatic and economic dimensions. The pandemic period also coincided with a sharp deterioration in bilateral trust between India and China, highlighted by the Galwan Valley clash and subsequent tensions along the Line of Actual Control, which deepened strategic mistrust and hardened India’s policy stance. The findings illuminate how political maneuvering has redefined China's geopolitical standing during this crisis, providing insights into the evolving landscape of Indo-Pacific relations. By uncovering these complexities, this study contributes to a nuanced understanding of health geopolitics and the underlying power dynamics.